Nasopharyngeal Carcinoma in Children: Clinical Cases - Mark E. Prokofyev; Nina O. Postanogova; Olga E. Nikonova ("Paediatrician" Publishers LLC, 2021)
Background. Nasopharyngeal cancer is rare malignant tumor of childhood. The clinical signs of this disease are rhinolalia, nasal breathing difficulties, headache and lymphadenopathy. There are no clinical cases of this nosology described previously in Russian literature. Clinical Cases Description. 1. Patient T., 11 years old, was moved from otolaryngology to oncology department due to CT findings of lump in the nasopharynx. At admission the child had complaints on fatigue, nasal  stuffiness, headache for past 3 months, pain in the neck at turning of his head. The histological study of this lump closing choanae at both sides was performed - nasopharyngeal carcinoma was revealed. 2. Patient A., 14 years old, was hospitalized in oncology department after self-admission to pediatric oncologist with complaints on rhinolalia for a month and jugular glands increase on both sides, weight loss (2 kilos) during last 3 months. Prior to this he was managed on outpatient basis and in infectious diseases department with the diagnosis "Infectious mononucleosis. EBV associated (antibodies (IgG) to capsid antigen of Epstein-Barr virus - 5.4 copies/ml), atypical moderate course". The generalized lymphadenopathy was revealed during examination in the oncology department. Multiple conglomerates of lymph nodes groups were revealed on CT scans. The histological study of biopsy sample from affected lymph node has shown metastases of nasopharyngeal carcinoma. The therapy according to the NPC-GPOH-2003 protocol was prescribed with marked positive dynamics after 3 months. Conclusion. The presence of headache, nasal breathing difficulties, body weight loss, fever in combination with lymphadenopathy in the neck  requires caution regarding nasopharyngeal cancer and in differential diagnosis with any other infectious or inflammatory diseases.